Testing Physical Activity Level as Determinant of Procrastination in Exercise: Will This Direction Work? - Yifei ZHAI , Yujun XUE , Huarui LI (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
China has witnessed massive economic development in the past few decades and one of the consequences of increased urbanization has been the reduction of physical activity in the adult population. In light of this trend, the researcher has conducted this study with the aim of examining how the low physical activity levels lead to exercise procrastination in the longer run by looking at data collected from Chinese adults that have at least a year or so experience of athletics of any type. The variables that were studied for this purpose in this research include the low level of physical activity as the independent variable, exercise procrastination as dependent and three mediating variable i.e. Low level of perceived self-efficacy in the athletes, perceived task difficulty in the athletes and negative affectivity in the athletes. The researcher conducted an in-depth literature review that led to the formation of 4 hypotheses for direct and indirect relationships. The researcher used positivism to conduct this quantitative research. The nature of research is exploratory with the random sampling technique used to conduct the survey. . Moreover, data is collected through an online questionnaire. The collected data was used to test the hypotheses through statistical and analytical procedures using SPSS. Various tests were applied including descriptive tests, KMO tests, CFA and SEM. The results of SEM showed that the direct impact of low physical activity was insignificant on exercise procrastination. As for the indirect effects, the mediation of negative affect and low self-efficacy were significant while that of perceived task difficulty was insignificant. In addition, the researcher has presented the limitations as well as the future directions that can be adopted in future researches.